Use of Video Laryngoscope in Sedated Spontaneously Breathing Patients with Predicted Difficult Tracheal Intubation and Impossibility of Using Fibreoptic Bronchoscopy - Alba Piroli; Ida Marsili; Franco Marinangeli; Silvia Costanzi; Luca Gentili; Antonella Paladini (Case Reports in Anesthesiology)
Intubation with a flexible fibrobronchoscope in an awake patient is frequently considered the technique of choice in patients with predicted difficult intubation. There are, however, situations in which the use of the fibrobronchoscope is not applicable, particularly due to problems attributable to the patient or to limited use of the instrument. In such situations, the video laryngoscope can be a useful alternative, as long as it is associated with adequate sedation of the patient. In fact, it ensures excellent viewing of the glottis, allowing for successful orotracheal intubation to be performed even in case of difficult airways, while keeping the patient spontaneously breathing throughout the procedure. From the data present in the literature, this technique seems to ensure a success rate and a safety profile similar to those obtained with the fibrobronchoscope, moreover, with greater ease of use by the anaesthesiologist. The main purpose of this work is to provide a valid and safe alternative to intubation with a fibrobronchoscope while awake in those patients with anticipated difficult airway management and in whom, for different reasons, fibrobronchoscope cannot be used.